A new approach to measuring economic policy shocks, with an application to conventional and unconventional monetary policy - Atsushi Inoue; Barbara Rossi (Quantitative Economics, 2021)
We propose a new approach to analyze economic shocks. Our new procedure identifies economic shocks as exogenous shifts in a function; hence, we call them "functional shocks." We show how to identify such shocks and how to trace their effects in the economy via VARs using "VARs with functional shocks" and "functional local projections." Using our new procedure, we address the crucial question of studying the effects of monetary policy by identifying monetary policy shocks as shifts in the whole term structure of government bond yields in a narrow window of time around monetary policy announcements. Our approach sheds new light on the effects of monetary policy shocks, both in conventional and unconventional periods, and shows that traditional identification procedures may miss important effects. Our new procedure has the advantage of identifying monetary policy shocks during both conventional and unconventional monetary policy periods in a unified manner and can be applied more generally to other economic shocks.
Keywords: D1; E21; E4; E52; H31; I3; 330; Identification; VARs; zero lower bound; unconventional monetarypolicy